Cerium oxide nanoparticles at the nano-bio interface: size-dependent cellular uptake. (12th November 2018) - Singh, Sushant; Ly, Anh; Das, Soumen; Sakthivel, Tamil S.; Barkam, Swetha; Seal, Sudipta
Abstract: The authors investigated the role of different size and morphology of cerium oxide nanoparticles (CNPs) in cellular uptake and internalization at the nano-bio interface. Atomic force microscopy (AFM) has been utilized to record changes in the membrane elasticity as a function of ceria particle morphology and concentration. Young's Modulus was estimated in presence and absence of CNPs of different sizes by gauging the membrane elasticity of CCL30 (squamous cell carcinoma) cells. Significant change in Young's Modulus was observed for CNP treatments at higher concentrations, while minimum membrane disruption was observed at lower concentrations. Studies using blocking agents specific to energy-dependent cellular internalization pathways indicated passive cellular uptake for smaller CNPs (3–5 nm). Other observations showed that larger CNPs were unable to permeate the cell membrane, which indicates an active uptake mechanism by the cell membrane. The ability of smaller CNPs (3–5 nm) to permeate the cell membrane without energy consumption by uptake pathways suggests potential for use as nanovectors for the delivery of bioactive molecules. Specifically, the passive uptake mechanism allows for the delivery of surface-bound molecules directly to the cytoplasm, avoiding the extreme chemical conditions of endosomal pathways.